Kewajiban Anak terhadap Orang Tua menurut Hadits Bukhari - Wildan Fauzi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to explain the obligations of children to parents according to the rights and arguments according to the Qur'an and hadith. This research is a qualitative type that applies literature study, the method of syarah hadith, and the tahlili approach. The results and discussion of this study include the rights and obligations of children to their parents, the traditions of children's obligations to their parents, and the syarah of hadiths of children's obligations to parents in the book of fathul bari. This study concludes that in the Bukhari hadith, it is very clearly explained about the obligations of children to their parents, how a child should treat parents, and what things a child should do to both parents in order to fulfill his obligations to parents. In the Qur'an and hadith, it is obligatory for children to give rights and obligations to both parents, such as providing a living, doing good, giving prayers to parents, giving love to both parents and respect for both parents. Islam has regulated as well as possible the obligations of children to parents, especially doing good (Birrul Walidain) and has been listed in the Qur'an Surah Al-Isra verses 23-24. This study recommends conducting further research on the obligations of children to parents in the form of field studies with the same approach and developed again.